Management of Material Stocks at the Motor Transport Enterprise : monograph - Bocharova, Nadezhda; Fedotova, Irina; Velichko, Jana (Sienciea Scripts, 2020)
The monograph focuses on the theoretical and practical aspects of managing material stocks at motor transport enterprises. It explores the role of inventory management in ensuring the uninterrupted functioning of transport operations, optimizing costs, and maintaining service quality. The study presents modern methods for forecasting demand, controlling stock levels, and streamlining supply processes. Emphasis is placed on the application of digital technologies, the integration of logistics systems, and the development of efficient inventory policies tailored to the specific needs of transport enterprises. The monograph offers practical recommendations for improving inventory turnover and enhancing operational efficiency.
Keywords: material stock management; motor transport enterprise; inventory control; logistics; supply chain; cost optimization; digital technologies; stock forecasting; operational efficiency; inventory turnover